Efficacy and Safety of Antioxidant Treatment With α-Lipoic Acid Over 4 Years in Diabetic Polyneuropathy: The NATHAN 1 trial - Ziegler, Dan; Low, Phillip A; Litchy, William J; Boulton, Andrew J.M; Vinik, Aaron I; Freeman, Roy; Samigullin, Rustem; Tritschler, Hans; Munzel, Ullrich; Maus, Joachim; Schütte, Klemens; Dyck, Peter J (Diabetes care, 2011)
OBJECTIVE: To evaluate the efficacy and safety of α-lipoic acid (ALA) over 4 years in mild-to-moderate diabetic distal symmetric sensorimotor polyneuropathy (DSPN). RESEARCH DESIGN AND METHODS: In a multicenter randomized double-blind parallel-group trial, 460 diabetic patients with mild-to-moderate DSPN were randomly assigned to oral treatment with 600 mg ALA once daily (n = 233) or placebo (n = 227) for 4 years. Primary end point was a composite score (Neuropathy Impairment Score [NIS]–Lower Limbs [NIS-LL] and seven neurophysiologic tests). Secondary outcome measures included NIS, NIS-LL, nerve conduction, and quantitative sensory tests (QSTs). RESULTS: Change in primary end point from baseline to 4 years showed no significant difference between treatment groups (P = 0.105). Change from baseline was significantly better with ALA than placebo for NIS (P = 0.028), NIS-LL (P = 0.05), and NIS-LL muscular weakness subscore (P = 0.045). More patients showed a clinically meaningful improvement and fewer showed progression of NIS (P = 0.013) and NIS-LL (P = 0.025) with ALA than with placebo. Nerve conduction and QST results did not significantly worsen with placebo. Global assessment of treatment tolerability and discontinuations due to lack of tolerability did not differ between the groups. The rates of serious adverse events were higher on ALA (38.1%) than on placebo (28.0%). CONCLUSIONS: Four-year treatment with ALA in mild-to-moderate DSPN did not influence the primary composite end point but resulted in a clinically meaningful improvement and prevention of progression of neuropathic impairments and was well tolerated. Because the primary composite end point did not deteriorate significantly in placebo-treated subjects, secondary prevention of its progression by ALA according to the trial design was not feasible.